Clinical effects of funcional appliances - Orrego C., Herbet M. (2005)
The funtional appliances therapy used wifh a correct diagnosis is able to make changes in teeth and in our patients profile .At the present time functional appliances can be used with or without fíxed appliances getting satisfactory results in malocclusions treatment.This report presents clinical cases in order to evaluate theraphy results in vertical ,transversal and sagital planes.